Down Bohicket Road : An Artist's Journey. Paintings and Sketches by Mary Whyte, With Excerpts from Alfreda's World. - Whyte, Mary (Book collections on Project MUSE., 2012)
A collection of poignant recollections celebrating the lives, friendships, and faith of Gullah women from Johns Island.